Residue behaviour and safety evaluation of fenaminstrobin in peanut field ecosystems. Issue 13 (21st October 2017) - You, Xiangwei; Sui, Chengcheng; Li, Yiqiang; Wang, Xiuguo; Xu, Jinli; Zheng, Xiao; Chen, Dan; Zhu, Guangyan
ABSTRACT: A rapid, sensitive, and selective method using a quick, easy, cheap, effective, rugged, and safe procedure in combination with high-performance liquid chromatography and tandem mass spectrometry was developed for the analysis of fenaminstrobin in peanut and soil. The average recoveries in all samples fall within 88.1%–10%, having relative standard deviations of 2.5%–14%. The limits of quantitation of fenaminstrobin in peanut shell, peanut kernels, peanut plant, and soil were 0.005, 0.004, 0.01, and 0.002 mg kg −1, respectively. The field trial results show that the half-lives of fenaminstrobin in peanut plant and soil are 1.3–10 and 5.5–20 days, respectively. Residues in peanut kernels were found to be present at <0.004 mg kg −1 levels, based on good agricultural practices recommended by the manufacturer. The risk posed by fenaminstrobin exposure at the recommended dosage is negligible to humans, depending on the risk quotient.